Design of a New Zirconia–Alumina–Ta Micro‐Nanocomposite with Unique Mechanical Properties. Issue 10 (30th August 2016) - Smirnov, Anton; Bartolomé, José F.; Kurland, Heinz‐Dieter; Grabow, Janet; Müller, Frank A.
Abstract : 2Y‐TZP/Al2 O3 hybrid nanoparticles prepared by CO2 laser covaporization (CoLAVA) were wet mixed with biocompatible lamellar Ta metal particles (20 vol%) and consolidated by spark plasma sintering. The microstructure and mechanical properties of this novel ceramic–metal composite have been studied. The achieved results demonstrate that both the homogeneity of the 2Y‐TZP/Al2 O3 nanocomposite matrix and the reinforcement with a micrometer‐sized ductile phase are prerequisites for the successful design and fabrication of ceramic–metal composites with high strength (1300 MPa), enhanced fracture toughness (16 MPa·m 1/2 ), and improved low‐temperature degradation resistance.